Interpretação e aplicação do direito tributário: fundamentos jurídicos da decisão - Dias, Ana Carolina Papacosta Conte de Carvalho (2010)
The main purpose of the present term paper is to provide a framework for a theory of the legally valid tax decision that assures the unity and consistency of the national tax system, based upon an analysis of interpretation, application and implementation of Tax Law. Positive law is understood to be a set of legal norms that exist within an historical context and determined territorial space. It is expressed through language, prescriptive propositions and legal messages for the purpose of regulating human conduct in interpersonal relations that are established in social reality, guided by the ideal of implementation of values that are foreseen by juridical phenomena, to guarantee the stability of interpersonal relations situated in social reality. Positive tax law, an expression that manifests the methodological cut necessary to cognoscente study of tax phenomenal is a language that forms the communicational system that creates legal tax phenomena. The Science of Tax Law is also a language that forms the communicational system that integrates the tax legal phenomena. The Languages of positive tax law and Tax Law Science form different communicational systems that co-exist and are co-related, since they are constituted by decisional acts (acts of speech) of subjects situated in a social context, a broader system within which communication may develop. The positive law tax system, founded on the juridical-epistemological principle of the fundamental norm, is a homogenous syntactically and semantically heterogeneous. When creating juridical phenomenal, one must guarantee the maintenance of normative expectations and the stabilization of intersubjective relations originated by the tax phenomenal. The interpretation is an intellective process of attribution of a signification to linguistic signs that form the statement, object of interpretation. For this reason, the present study uses the concepts of the General Theory of Law, analyzed by the premises developed by Contemporary Philosophy of Language and by the other sciences of language. The authentic interpretation acts of decision from competent subjects creates and realizes tax law. Because it is an act of decision, the authentic interpretation is submitted to the subjectivity of the competent subject (valuation process), that must be limited (objective) by the procedures foreseen in the tax system, which, in the final analysis, point to an interpretative technique based upon intertextuality and dialogism. The final interpretant of Tax Law indispensable for the realization of tax phenomena is the set of prescriptive enunciations handed down by the Supreme Court, guardian of the Federal Constitution, introductory norm of the legal rules which comprise the National Tax System. Its function is to build a correct interpretation from the constitutional enunciates. The texts enunciated by its decisions are the physical supports (that dialogue with the other juridical texts), the starting point for all interpretation performed by authentic interpreters of positive tax law. The Science of Tax Law, formed by descriptive propositions, developed by the decisions of interpreters, acts of speech, enunciations that come from prescriptive tax law assertions, is meta-interpretation of tax law and serves as physical support, the starting point of interpretation, comprising also the intertextuality upon which the Supreme Court bases its decisions. Interpretation is the creator, applicator, and implementer of tax law. It is a translation mechanism of the messages coming from other social systems (principally from the Science of Tax Law System) in Tax Law, allowing it to coordinate the flux of human interaction, propagating the sensation of foreseeability regarding the juridical effects of tax phenomena